SIVALHIPPUS NAGRIENSIS (EQUIDAE, MAMMALIA) FROM DHOK PATHAN FORMATION OF SIWALIKS, PAKISTAN - M. A. Babar; M. A. Khan; I. Munawar; K. Mahmood; S. G. Abbas; M. Akhtar (Journal of Animal and Plant Sciences, 2016)
The described specimens have been collected from the Dhok Pathan Formation of the Siwaliks, northern Pakistan. The new material consists of the isolated dentition and reflects morphological features of Sivalhippus nagriensis. The specimens were observed and compared with the previous data. The new discovered material found from the Dhok Pathan type locality identifies the species Sivalhippus nagriensis. The new sample contributes additional information about the species Sivalhippus nagriensis.
Keywords: Mammalia; Perissodactyla; Fossils; Miocene; Pliocene; Pleistocene; Siwaliks